PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA ANTARA PEMBELAJARAN BERBASIS MASALAH DENGAN PENEMUAN TERBIMBING DI SMP NEGERI 5 STABAT - Riskyka . (Jurnal Sintaksis, 2019)
This research aims to know: (1) the differences of problems solving mathematics ability between the students who taught problem-based learning with guided discovery, (2) the interaction between the learning model and the initial ability of mathematics towards problem-solving mathematis ability. This research is a quasi-experimental research. The research population was eighth grade junior high school students of SMP Negeri 5 Stabat, then have two classes of ninth grade. The instrument used test of problems solving mathematics ability. Data analysis is used by analysis of variance (ANOVA) two lines. The results showed that (1) there are differences of problems solving mathematics ability between between the students who taught problem-based learning with guided discovery, where the application of problem based learning model is better than students who received learning guided discovery to problems solving mathematics ability, (2) there is no interaction between the learning model and initial ability of mathematics towards problem-solving mathematics ability. This shows that the contribution of jointly given by learning model with the initial ability of mathematics students do not have a significant effect on the development of students‘s problems solving mathematics ability.